Effect of Very Low-Dose Hydrocortisone on Shock Reversal in Patients With Septic Shock. (April 2020) - Sbertoli, Robert; Hu, Zeyu; Henke, Jonathan; Wu, Eric; Santosh, Shrihari; Osmon, Stephen; Charbek, Edward; Jamkhana, Zafar; Santosh, Sadashiv
Abstract : Objectives: In patients with septic shock, hydrocortisone 200–400 mg/d has been shown to reverse shock compared with placebo. Lower doses of hydrocortisone have not previously been studied, and there are no previous studies comparing two different doses of hydrocortisone. At our institution, some clinicians routinely prescribe doses less than 200 mg/d. This study aims to compare the effect of lower doses of hydrocortisone to standard doses on shock reversal and adverse events in septic shock. Design: Retrospective cohort study. Setting: Single-center medical ICU. Subjects: Patients who received hydrocortisone for septic shock. Interventions: Electronic chart review. Measurements and Main Results: Patients were divided into low-dose hydrocortisone (75–150 mg/d) and standard-dose hydrocortisone (200–400 mg/d) cohorts based on initial prescribed hydrocortisone dose. Rates of shock reversal and adverse events in the two cohorts were compared. Two-hundred thirteen patients were included—41 in low-dose and 172 in standard-dose cohorts. Baseline characteristics including initial vasopressor requirement and Sequential Organ Failure Assessment scores were similar. Average rates of change in vasopressor needs, conditional hazard rate for vasopressor withdrawal, and cumulative probability for vasopressor withdrawal were all quantitatively similar for low-dose and standard-dose hydrocortisone. Insulin requirement (particularly in those with diabetes mellitus), blood glucose in those with diabetes mellitus, and frequency of secondary infections seemed to be lower in the low-dose hydrocortisone cohort. Mortality and other secondary outcomes were similar. Conclusions: In septic shock, hydrocortisone dosed 75–150 mg/d appears to reverse shock as effectively 200–400 mg/d and may cause a lower frequency of adverse events. Abstract : Supplemental Digital Content is available in the text.